SURVIVAL IN THE FIRST HOURS OF THE CENOZOIC - Robertson D.S.; McKenna M.C.; Lillegraven J.A.; Toon O.B.; Hope S. (My University, 2004)
For several hours following the Chicxulub impact, the entire Earth was bathed with intense infrared radiation from ballistically reentering ejecta. The global heat pulse would have killed unsheltered organisms directly and ignited fires at places where adequate fuel was available. Sheltering underground, within natural cavities, or in water would have been a necessary but not always sufficient condition for survival. Survival through sheltering from an initial thermal pulse is not adequately considered in literature about Cretaceous-Tertiary nonmarine extinctions. We compare predicted intense, short-term, thermal effects with what is known about the fossil record of nonmarine vertebrates and suggest that paleontological evidence of survival is compatible with theoretical results from bolide physics.
Keywords: bolide physics; Chicxulub; Cretaceous; evolution; extinction; extraterrestrial impact; infrared radiation; nonmarine; Paleocene; survival; Tertiary; vertebrates; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен